KESIAPAN STANDAR OPERASIONAL MANAJEMEN SEBAGAI DASAR KESIAPAN MENGADOPSI INDUSTRI 4.0: STUDI KOPERASI SYARIAH DI JAWA BARAT INDONESIA - Hennidah Karnawati; Koernia Purwihartuti; Tia Fahmi Angestiwi; Kristianingsih (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
The aim of this research is evaluates the management operational standard and the level of readiness of Sharia Cooperatives in West Java for adopting the Industrial 4.0. Method: descriptive surveyed to 191 sharia cooperative practitioners,interviewed the leaders of 39 sharia cooperatives,reviewed sharia government regulations including MUI Fatma. The data processing used descriptive analysis. Result: Empirical facts show that all sharia cooperatives already have management operational standard but not yet connected with the readiness to adopt industry 4.0; then the highest ready indicator is “consistently to AD/ART, SOM, SOP, and policy patterns while the lowest ready is “use of Electronic signatures as a verification and authentication tool.” Conclusion: The management operational standard should be always adjusted with the provisions for the use of technology to provide maximum services. The implication of this research that government issues policies for Islamic cooperative managers to implement management operational system (MOS), containing provisions that require IoT technology.